2019
DOI: 10.1038/s41388-019-0815-5
|View full text |Cite
|
Sign up to set email alerts
|

BET bromodomain inhibition blocks the function of a critical AR-independent master regulator network in lethal prostate cancer

Abstract: BET bromodomain inhibitors block prostate cancer cell growth at least in part through c-Myc and androgen receptor (AR) suppression. However, little is known about other transcriptional regulators whose suppression contributes to BET bromodomain inhibitor anti-tumor activity. Moreover, the anti-tumor activity of BET bromodomain inhibition in AR-independent castrationresistant prostate cancers (CRPC), whose frequency is increasing, is also unknown. Herein, we demonstrate that BET bromodomain inhibition blocks gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Prior work demonstrated that BETi is a promising approach to block growth of AR-driven tumors (37), and we recently extended these findings and confirmed the anti-tumor activity of BETi in AR-null adenocarcinoma CRPC (34,38). Thus, we sought to determine the anti-tumor These LuCaP cultures do not proliferate well long-term, but BETi treatment using concentrations < 1 µM of either agent led to cell death (Supplemental Figure S5G).…”
Section: Bet Bromodomain Inhibition Blocks E2f1 Function T-nepc Lineage Plasticity Gene Expression and T-nepc Cell Survivalmentioning
confidence: 60%
See 2 more Smart Citations
“…Prior work demonstrated that BETi is a promising approach to block growth of AR-driven tumors (37), and we recently extended these findings and confirmed the anti-tumor activity of BETi in AR-null adenocarcinoma CRPC (34,38). Thus, we sought to determine the anti-tumor These LuCaP cultures do not proliferate well long-term, but BETi treatment using concentrations < 1 µM of either agent led to cell death (Supplemental Figure S5G).…”
Section: Bet Bromodomain Inhibition Blocks E2f1 Function T-nepc Lineage Plasticity Gene Expression and T-nepc Cell Survivalmentioning
confidence: 60%
“…The anti-tumor activity of BETi in CRPC has been primarily linked to suppression of AR function (37,49). However, we recently demonstrated that BETi also blocks the growth of ARnull adenocarcinoma CRPC tumors in pre-clinical studies (34,38) and growth of patient tumors that responded poorly to enzalutamide or abiraterone-many of which are AR activity-low (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data in pre-clinical studies revealed that BET inhibitors exert potential anti-tumor effects in non-small cell lung cancer cells [27], mixed-lineage leukemia gene-fused leukemia [28], and other solid tumors including pancreatic ductal adenocarcinoma [29], prostate cancer [30]. In several subtypes of breast cancer, BET inhibitors have been shown to display a strong anti-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with EP300/CREBBP inhibitors not only reduced AR but also MYC signaling. 51 Although the current study focused on inhibition of EP300/CREBBP in association with MYC/ribosomal protein regulation, other possible actions of these inhibitors should be mentioned. Recently, Fan et al 52 reported that enzalutamide-resistant C4-2 cells are more sensitive to either BET or EP300/CREBBP inhibitors than parental cells.…”
Section: Ribosomal Proteins In Prostate Cancermentioning
confidence: 98%